A Covert Timing Channel via Algorithmic Complexity Attacks: Design and Analysis - Xiaoshan Sun; Liang Cheng; Yang Zhang (2011 IEEE International Conference on Communications (ICC), 2011)
A covert channel is a communication channel that bypasses the access controls of the system, and it is a threat to the system's security. In this paper, we propose a new covert timing channel which exploits the algorithmic complexity vulnerabilities in the name lookup algorithm of the kernel. This covert channel has a high capacity and it is practically exploitable. In our experiments, the data rate reaches 2256 bps under a very low error rate. This data rate is high enough for practical use. So our covert channel is dangerous. To our knowledge, no previous works propose this covert channel nor implement it. We describe our design and implementation of the covert channel on a SELinux system, discuss the subtle issues that arose in the design, present performance data of the covert channel and analyse its capacity.